Moderately Transparent Chitosan-PVA Blended Membrane for Strong Mechanical Stiffness and as a Robust Bio-Material Energy Harvester Through Contact-Separation Mode TENG - Ravi Kumar Cheedarala; Jung Il Song (Frontiers in Nanotechnology, 2021)
The detection of sustainable materials from naturally available resources using a simple fabrication process is highly important for novel research. Here, we used chitosan-PVA (Chs-PVA) blend films via layer-by-layer casting technologies for generating power through mechanical induction through triboelectric nanogenerators. The proposed Chs-PVA biodegradable film (i.e., thickness of 60 ± 5 μm) is facile, ecofriendly, highly flexible, mechanically strong, cost-effective, and easy to scale up. FT-IR analysis of the ChS-PVA blend membrane showed the strong interactions between the amines of ChS and hydroxyl groups of PVA through chemical cross-linking by hydrogen bonding. More importantly, the triboelectric nanogenerators (TENG) values of ChS-PVA films were 3–4 orders of magnitude lower than chitosan films reported before. Layer-on-layer cast films in particular exhibited high tensile strength (15.8 ± 1 MPa) and were more than three times stronger than other polyelectrolyte multilayer films. Both types of films remained stable in an acidic environment. Furthermore, the layer-on-layer-assembled films presented greater open circuit voltage (Voc) and short circuit current (Isc) values compared to pure ChS and PVA films. The ChS-PVA membrane can be used as a functional layer to produce charges by collecting get-up-and-go through vertical contact and separation mode TENG counters to the PVDF membrane. The enhancement of Voc and Isc of ChS-PVA TENG were 244 and 1,080% from ChS TENG. Where in the case of PVA TENG, the enhancement of Voc and Isc were increased by 633 and 2,888%, respectively due to the availability of free loan pair on the -NH2 and -OH functional groups. The novel ChS-PVA TENG is a potential candidate for satisfying the tight requirement of an optimized energy harvesting device as an alternate bio-material option for contact-separation mode TENGs.